2021
DOI: 10.12973/eu-jer.10.3.1359
|View full text |Cite
|
Sign up to set email alerts
|

Online English Comics as Reading Materials for English Language Education Department Students

Abstract: <p style="text-align: justify;">Online English comic is one of reading material that can be used by students. Students should be triggered by interesting and understandable reading material to increase their reading motivation and English proficiency. The objective of this study is to discuss the benefits of online English comics as reading materials and to discover the applications and websites that are usually used by students to read online English comics. This study applied the descriptive qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
5
0
1
Order By: Relevance
“…The researcher concluded that authentic materials boost students' vocabulary based on the findings of the study and conversation. These findings are pertinent and support prior research by Ranker, 2007;Apriani et al, 2014;Rokhayani & Utari, 2014;Cimermanová, 2015;Issa, 2018;Nurkholida, 2018;Fatimah et al, 2019;Ahsanah & Utomo, 2020;Robbani & Khoirotunnisa, 2021. As a consequence, the findings of this study can be used as a resource for authentic information to help students enhance their vocabulary mastery.…”
Section: Hypothesis Testingsupporting
confidence: 87%
“…The researcher concluded that authentic materials boost students' vocabulary based on the findings of the study and conversation. These findings are pertinent and support prior research by Ranker, 2007;Apriani et al, 2014;Rokhayani & Utari, 2014;Cimermanová, 2015;Issa, 2018;Nurkholida, 2018;Fatimah et al, 2019;Ahsanah & Utomo, 2020;Robbani & Khoirotunnisa, 2021. As a consequence, the findings of this study can be used as a resource for authentic information to help students enhance their vocabulary mastery.…”
Section: Hypothesis Testingsupporting
confidence: 87%
“…Extrinsic motivation is the learner's external drive for reading, which is shaped by factors such as the type of material, the learner's level of English proficiency, and their vocabulary knowledge (Roomy & Alhawsawi, 2018;Robbani & Khoirotunnisa, 2021;Insuasty, 2020). This aligns with the sociocultural theory of learning (Vygotsky, 1978), which emphasizes the importance of social factors in learning.…”
Section: Discussionmentioning
confidence: 92%
“…Extrinsic motivation is the learner's external drive for reading, which is shaped by factors such as the type of material, the learner's level of English proficiency, and their vocabulary knowledge (Roomy & Alhawsawi, 2018;Robbani & Khoirotunnisa, 2021;Insuasty, 2020).…”
Section: Students Of English As Second Languagementioning
confidence: 99%
“…The level of partial multimodality is characterized by the predominance of visual content, when the author transmits a message and the reader receives it. The most important feature of partial multimodality is that only under the condition of combining visual and verbal content, the real amount of information conveyed by the comic paper increases (Rakhmawati, 2018).…”
Section: Source: Compiled By the Authorsmentioning
confidence: 99%